‘Sekolah Lapang Petani’: Membangun Komitmen, Disiplin dan Kretivitas Petani Melalui SLP-PHT - Munsi Lampe (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2016)
AbstractAlthough the Green Revolution in Indonesia has shown an increase in theagriculturalproduction, a rapid marginalisation process among the farmers has taken place simultaneously.This article aims to identify the role of Sekolah Lapang Petani (Farmer Field School), which isone of the programs conducted byPengelolaan Hama Terpadu (Integrated Pest Management,IPM). This program is conducted by the government in response to the negative impacts of theGreen Revolution that is consideredto be responsible in deteriorating the local knowledge andthe local wisdom techniques, the power of creative-innovation and the freedom of the farmers.This study was conducted in two different sites in South Sulawesi, namely: Manjalling Village(Gowa) and Soreang Village (Maros). Our informants are those who joined SLP-PHT programin the two locations. They consistof 17 farmers; 5 of them are from Manjalling, while rests arefrom Soreang. We triangulate, in-depth interview, observation, life history, and focus groupdiscussion (FGD) as our data collection methods.The results showed that the implementation of SLP-PHT program in Manjallingand Soreanghas played an important role in the application process of the local knowledge and the farmers’creative-innovative development in agricultural, such as productive, righteousness, adaptive,and environmentally friendly.Keywords: farmer field school, creativity, innovative, plant fertilizer and medicine.